Indonesia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1997)
This paper reviews economic developments in Indonesia during 1996-97. The Indonesian economy continued to perform well in 1996, with real GDP growth of 7.8 percent. The rate of inflation fell to 5 percent in 1996/97, assisted by improved food supplies and generally subdued import prices. A budgetary surplus of 1 percent of GDP was estimated for 1996/97, reflecting higher-than-projected oil revenue and firm expenditure control. However, broad money and private sector credit growth were 27 percent and 24 percent, respectively, in the face of strong private capital inflows.